Application of family-centered empowerment model in primary caregivers of premature infants: A quasi-experimental study - Dai, Kun; Fan, Xinqi; Shi, Huan; Xiong, Xiaoju; Ding, Lingli; Yu, Yaqi; Yu, Genzhen; Wang, Suqing (Frontiers in Pediatrics, 2023)
Objective: To explore the effect of the family-centered empowerment model (FECM) on reducing anxiety, improving care ability, and readiness for hospital discharge of main caregivers of preterm infants. Methods: The primary caregivers of preterm infants who were admitted to the Neonatal intensive care Unit (NICU) of our center from September 2021 to April 2022 were selected as the research objects. According to the wishes of the primary caregivers of preterm infants, they were divided into group A (FECM group) and group B (non-FECM group). The intervention effects were evaluated with the Anxiety Screening Scale (GAD-7), the Readiness for Hospital Discharge Scale-Parent Version (RHDS-Parent Form), and the Primary Caregivers of Premature Infants Assessment of Care Ability Questionnaire. Results: Before the intervention, there was no statistically significant difference in the general information, anxiety screening, the scores of each dimension and total score of the comprehensive ability of the main caregivers, and the score of caregiver preparedness between the two groups (P > 0.05). After the intervention, there were statistically significant differences in the anxiety screening, the total score and total score of each dimension of the care ability, and the score of caregiver preparedness between the two groups (P < 0.05). Conclusions: The FECM can reduce the anxiety of the main caregivers of preterm infants and improve their care ability and readiness for hospital discharge.